Cultural Competency Assessment in Nursing Students - Rivas Zambrano, Jennifer Alexandra (2024)
Introduction: The wide variety of health services and the diversity of ethnic groups in Ecuador represent a significant challenge for the training of future nursing professionals with adequate skills to provide comprehensive and quality care. Objective: To evaluate the level of Cultural Competence in final year nursing students. Method: Study with a quantitative approach, through the cross-sectional observational method, a universe of 172 students studying the last year of the nursing career was obtained, working with a sample of 120 students with a 95% confidence level and margin of error of 5%. The Papadopoulos cultural competencies scale was used, which consists of 40 items classified into 4 domains. For the analysis of the data, SPSS software for Windows version 26.0 was used. Calculations of descriptive statistics were kept, such as means, standard deviations, frequency and percentage. Results: Students demonstrate greater development in the domain related to competencies related to cultural practice (M 4.25 ± 0.85) while the less developed is related to the competencies developed related to the cultural awareness domain (M 4.14 ± 0.93). Cronbach's alpha of the applied instrument was 0.99. Conclusions: Students demonstrated a relatively high level of cultural competence. The tool presented in this study has proven to be valid and reliable for application with undergraduate nursing students.